KAJIAN HUKUM PASAL 27 UNDANG-UNDANG NO 19 TAHUN 2016 - Syahrul Bakti Harahap, Herlina Hanum Harahap (LP2M Universitas Muslim Nusantara Al Washliyah, 2020)
Based on Article 1 Paragraph (1) Of Law N0. 19. 0f 2016 in conjungtion with Law of 2008, conserming Elektronik Information Transaktion, namely, electronic information one or a set of elektonic data,including but now limited to voce writing, images, maps, designs, photos, electronic and interchange (EDI), electronic mail, telegram, telecopy,or the like, letters, signs, numbers, access codes, symbol or corporation that have beep processed wich have meaning can be understood by thos who are able to understand them. This study aims to determine andanalyze how the level of understanding of Islamic Azizi Medan private high school student regarding Article 27 of Law No. 9/2016, and to find out and anlize haw saction are given to students of Medan Azizi Privat Haigh school if the violate Article Law No. 19 year 2016, The hypothesisi in the students of Islamic Privatte High school Azizi Medan understanding Article 27 of Law No. 19 Year 2016, conserming Electronic Information andTransaction. This study uses empirical juridisial research metodes, or direct research using data collection tool through question and interviews. Darwing conclusion by means of deskriftive qualitive, This research was conducted in IslamicPrivate High School Azizi Medan. The saples in this study were studens of the Islamic Private High School Azizi Medan. From the result of research do Islamic Private Hig School studens Azizi Medan, 60%(sixty persent) do understand a bout Article 27 ofLaw No. 16 year2019.